Analysis of Competency, Entrepreneurship Orientation, and Performance in Bandar Lampung Furniture Industry - Arifin, Triyono; Dwiono, Sugeng; Rudihartati, Leny (Journal of Business and Economics Research (JBE), 2024)
This research aims to evaluate the impact of entrepreneurial competencies and entrepreneurial orientation on the performance of the furniture industry in Bandar Lampung City, as well as to assess the mediating effect of entrepreneurial orientation in this relationship. Primary data were obtained through a cross-sectional survey with direct interviews using questionnaires targeted at furniture business owners. The research sample consisted of 235 furniture businesses, representing 10% of the population. Validity was tested using Confirmatory Factor Analysis (CFA) and reliability was measured with Cronbach's Alpha. The analysis method applied was hierarchical regression. The research findings indicate that (1) Model 1 is the best model for explaining the relationship between entrepreneurial competencies and entrepreneurial orientation with SME performance, (2) entrepreneurial competencies (initiative and entrepreneurship, planning and organizing, technology) and entrepreneurial orientation have a positive and significant influence on performance, and (3) entrepreneurial orientation mediates the relationship between entrepreneurial competencies and furniture business performance in Bandar Lampung.